Truck loaded with teenage girls - Unknown:::Creator::::::::::::
Photograph shows an old truck loaded with group of girls in it's bed and three in the cab in front of the YWCA's annex. They are in the street in front of the YWCA's annex and the sign above the visible doorway arch reads YWCA.